Encrypting Numbers through Square Grid Graphs - Shobana, L. (International Journal of Engineering and Technology, 2018)
Cryptography emphasizes the mathematics behind the theory of public key cryptosystems and digital signature schemes. Encryption is essential for ensured and trusted delivery of sensitive information whereas the decryption is the process of decoding the data which has been encrypted in to a secret format. An authorized user can only decrypt data since decryption requires a secret key or password. There are several methods to encrypt the numbers. In this paper, a combinatorial technique to encrypt and decrypt numbers through labeled strong face of a square grid graph using residue class of Z3 has been investigated.Â